1999
DOI: 10.1093/genetics/152.3.909
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitive and Mitotic Recombination Phenotypes of the Saccharomyces cerevisiae dun1 Mutant Defective in DNA Damage-Inducible Gene Expression

Abstract: The biological significance of DNA damage-induced gene expression in conferring resistance to DNA-damaging agents is unclear. We investigated the role of DUN1-mediated, DNA damage-inducible gene expression in conferring radiation resistance in Saccharomyces cerevisiae. The DUN1 gene was assigned to the RAD3 epistasis group by quantitating the radiation sensitivities of dun1, rad52, rad1, rad9, rad18 single and double mutants, and of the dun1 rad9 rad52 triple mutant. The dun1 and rad52 single mutants were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Dun1-dependent Srs2 phosphoryl-ation might be explained in view of recent results that have pointed out a role for Dun1 in channelling DNA repair into a non-recombinogenic pathway (Fasullo et al, 1999). Since Srs2 plays a similar role (Aboussekhra et al, 1989), it has been suggested that the higher rate of mitotic recombination observed in Ddun1 mutants might result from the inability to phosphorylate speci®c repair proteins, such as the Srs2 helicase (Fasullo et al, 1999). Although we cannot exclude the possibility that Srs2 is a direct substrate of Dun1, we would like to suggest that the pathway dependent upon Mec1, Rad53 and possibly Dun1 acts to modulate Cdk1, which, either directly or indirectly, would cause Srs2 phosphorylation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Dun1-dependent Srs2 phosphoryl-ation might be explained in view of recent results that have pointed out a role for Dun1 in channelling DNA repair into a non-recombinogenic pathway (Fasullo et al, 1999). Since Srs2 plays a similar role (Aboussekhra et al, 1989), it has been suggested that the higher rate of mitotic recombination observed in Ddun1 mutants might result from the inability to phosphorylate speci®c repair proteins, such as the Srs2 helicase (Fasullo et al, 1999). Although we cannot exclude the possibility that Srs2 is a direct substrate of Dun1, we would like to suggest that the pathway dependent upon Mec1, Rad53 and possibly Dun1 acts to modulate Cdk1, which, either directly or indirectly, would cause Srs2 phosphorylation.…”
Section: Discussionmentioning
confidence: 98%
“…Dun1 has been placed downstream of Rad53 (Zhou and Elledge, 1993) and our data indicate that Srs2 phosphorylation is abolished in Ddun1 mutant cells. Dun1-dependent Srs2 phosphoryl-ation might be explained in view of recent results that have pointed out a role for Dun1 in channelling DNA repair into a non-recombinogenic pathway (Fasullo et al, 1999). Since Srs2 plays a similar role (Aboussekhra et al, 1989), it has been suggested that the higher rate of mitotic recombination observed in Ddun1 mutants might result from the inability to phosphorylate speci®c repair proteins, such as the Srs2 helicase (Fasullo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eukaryotic cells have evolved multiple strategies to tolerate genomic damage. These include DNA repair systems that remove or bypass potential mutagenic DNA lesions ( , ) and cell cycle delays at multiple transition points after exposure to DNA damaging agents ( ). Weinert and Hartwell () first observed the control of these delays in budding yeast and called them DNA checkpoints.…”
mentioning
confidence: 99%